AB0695 LONG-TERM OUTCOMES OF AFRICAN AMERICAN PATIENTS WITH SYSTEMIC SCLEROSIS-RELATED INTERSTITIAL LUNG DISEASE. (June 2019) - Volkmann, Elizabeth; Ning, LI; Khanna, Dinesh; Clements, Philip; Furst, Daniel; Assassi, Shervin; Roth, Michael; Elashoff, Robert; Tashkin, Donald
Abstract : Background: Observational studies have demonstrated that african american patients with Systemic Sclerosis (SSc) have a more unfavorable prognosis compared with non-African americans. However, no studies have evaluated racial disparities using data from a randomized controlled trial (RCT) where all patients have equal access to care and standard treatment and follow-up during the trial. Objectives: To compare morbidity and mortality in african american and non-African american patients who participated in the Scleroderma Lung Study (SLS) I and II. 1, 2 Methods: SLS I randomized 158 SSc patients with interstitial lung disease (ILD) from 13 US SSc centers to 1 year of oral CYC (cyclophosphamide) versus placebo. SLS II randomized 142 SSc-ILD participants from 14 US SSc centers to 1 year of oral CYC, followed by 1 year of placebo, versus 2 years of mycophenolate (MMF). Up to 12 (SLS I) and 5 (SLS II) years after randomization, we contacted enrolled patients or designated surrogates to assess the following: mortality, cause of mortality, and development of organ failure. We used cox proportional hazard modeling to determine the variables associated with survival. Results: Baseline characteristics of the SLS I and II cohorts were similar. In SLS I, african american participants (N=26) were younger than non-African american participants (N=132) (43.1 vs. 49.5 years, P=0.015). In SLS II, african american participants (N=33) had slightly increased baseline forced vital capacity (FVC) (69.2 vs 65.6, P=0.038), compared with non-American american participants (N=109). There were no significant baseline differences in the extent of cutaneous sclerosis (Modified Rodnan Skin Score [MRSS]), presence of diffuse cutaneous disease or serological profiles between racial groups. After adjusting for age, MRSS, FVC, there was no difference in long-term mortality outcomes (due to all causes or due to respiratory failure) in african american versus Non-African american SSc-ILD participants in SLS I or II (Figure 1 ). There was also no difference in time to the development of respiratory failure in african american versus Non-African american SSc-ILD participants in SLS I or II. Conclusion: Data from two of the largest RCTs in SSc-ILD demonstrated that african american patients with SSc-ILD have similar morbidity and mortality outcomes compared with non-African american SSc-ILD patients, even after adjusting for age and baseline disease severity. These findings contrast with the racial disparities described in previous observational studies and warrant further investigation. References: [1] Tashkin, et al. NEJM2006;354:2655. [2] Tashkin, et al. Lancet Resp Med2016;4:708. Figure 1a . Time to death in african american participants of SLS I (red line) and non-African american participants of SLS I (blue line). Figure 1b . Time to death in african american participants of SLS II (red line) and non-African american participants of SLS II (blue line). Disclosure of interests: Elizabeth Volkmann Shareholder of: Pfizer, inc., Consultant for: Boehringer ingelheim, Speakers bureau: Boehringer ingelheim, Ning Li: None declared, Dinesh Khanna Shareholder of: Eicos Sciences, inc, Grant/research support from: Bayer, BMS, Pfizer, Horizon, Consultant for: actelion acceleron, arena, Bayer, BI, BMS, CSL Behring, Corbus, Cytori, GSK, Genentech/Roche, Galapagos, Employee of: Elcos Sciences, inc, Philip Clements: None declared, Daniel Furst Grant/research support from: F. Hoffmann-La Roche, Genentech, Shervin assassi: None declared, Michael Roth Grant/research support from: Genentech/Roche, Robert Elashoff: None declared, Donald Tashkin Consultant for: EMD Serono